2010
DOI: 10.1016/j.neuroimage.2010.05.067
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal functional connectivity of default mode sub-networks in autism spectrum disorder patients

Abstract: Autism spectrum disorders (ASDs) are characterized by deficits in social and communication processes. Recent data suggest that altered functional connectivity (FC), i.e. synchronous brain activity, might contribute to these deficits. Of specific interest is the FC integrity of the default mode network (DMN), a network active during passive resting states and cognitive processes related to social deficits seen in ASD, e.g. Theory of Mind. We investigated the role of altered FC of default mode sub-networks (DM-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
482
10
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 578 publications
(567 citation statements)
references
References 70 publications
55
482
10
4
Order By: Relevance
“…Assaf et al, 2010). Many studies have reported decreased FC between DMN regions in those with ASD (Assaf et al, 2010;Kennedy & Courchesne, 2008;Monk et al, 2009;Weng et al, 2010), although hyperconnectivity within this network has also been reported (Monk et al, 2009;Uddin et al, 2013a). One study found that hypo-or hyperconnectivity of the DMN may be region-specific (Doyle-Thomas et al, 2015).…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 99%
See 1 more Smart Citation
“…Assaf et al, 2010). Many studies have reported decreased FC between DMN regions in those with ASD (Assaf et al, 2010;Kennedy & Courchesne, 2008;Monk et al, 2009;Weng et al, 2010), although hyperconnectivity within this network has also been reported (Monk et al, 2009;Uddin et al, 2013a). One study found that hypo-or hyperconnectivity of the DMN may be region-specific (Doyle-Thomas et al, 2015).…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 99%
“…The DMN has been a focus of many FC studies in those with ASD, particularly because it has been hypothesized that abnormal DMN functioning relates to decreased self-referential processing, a decreased ability to redirect attention from external to internal processing, and difficulties with theory of mind in ASD (e.g. Assaf et al, 2010). Many studies have reported decreased FC between DMN regions in those with ASD (Assaf et al, 2010;Kennedy & Courchesne, 2008;Monk et al, 2009;Weng et al, 2010), although hyperconnectivity within this network has also been reported (Monk et al, 2009;Uddin et al, 2013a).…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 99%
“…For example, schizophrenia appears to be associated with reduced DMN connectivity in all subsystems of the network 27 , and this has been correlated with subsystem-specific deficits in cognitive processes 28 . Likewise, in MDD 64 , OCD, 65 and autistic spectrum disorders 66 , respectively, there is emerging evidence of disorder-specific abnormalities that may be tied to individual subcomponents of the DMN. To our knowledge, no empirical study has directly compared DMN connectivity across a range of clinical groups to test the specificity (or otherwise) of DMN disturbances.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…No study to our knowledge has yet to examine the baseline neural processes that characterize the architecture of functional connectivity in youths with 22q11DS. Such studies may indeed be important, especially because recent investigations in other pediatric populations show that atypical functional connectivity contributes to the emergence of neurodevelopmental psychiatric disorders (Assaf et al, 2010;Fair et al, 2010).…”
Section: Introductionmentioning
confidence: 99%